2017
DOI: 10.1155/2017/3078194
|View full text |Cite
|
Sign up to set email alerts
|

Saliva-Derived Host Defense Peptides Histatin1 and LL-37 Increase Secretion of Antimicrobial Skin and Oral Mucosa Chemokine CCL20 in an IL-1α-Independent Manner

Abstract: Even though skin and oral mucosae are continuously in contact with commensal and opportunistic microorganisms, they generally remain healthy and uninflamed. Host defense peptides (HDPs) make up the body's first line of defense against many invading pathogens and are involved in the orchestration of innate immunity and the inflammatory response. In this study, we investigated the effect of two salivary HDPs, LL-37 and Hst1, on the inflammatory and antimicrobial response by skin and oral mucosa (gingiva) keratin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 40 publications
2
25
0
Order By: Relevance
“…58 Previously we have described intrinsic differences between skin and gingiva with regard to innate immunology, wound healing, and the response to contact sensitizers. 48,[59][60][61] In current study, under unexposed conditions, we show that RHS secretes higher baseline levels of cytokines involved in LC migration (IL-18 and CXCL12) than RHG, which is in line with our previous study, 25,48 and we also show that S. mitis increased the cytokine release of IL-6, CXCL8, CCL5, and CCL20 in RHS but not in RHG. Such relative inertness of RHG to S. mitis is supported by findings of others describing the regulatory role of S. mitis as an oral commensal on immune balance, where it inhibits CD 4+ T cell proliferation, promotes Th17 responses, and induces the secretion of IL-10 in human monocytes.…”
Section: Discussionsupporting
confidence: 92%
“…58 Previously we have described intrinsic differences between skin and gingiva with regard to innate immunology, wound healing, and the response to contact sensitizers. 48,[59][60][61] In current study, under unexposed conditions, we show that RHS secretes higher baseline levels of cytokines involved in LC migration (IL-18 and CXCL12) than RHG, which is in line with our previous study, 25,48 and we also show that S. mitis increased the cytokine release of IL-6, CXCL8, CCL5, and CCL20 in RHS but not in RHG. Such relative inertness of RHG to S. mitis is supported by findings of others describing the regulatory role of S. mitis as an oral commensal on immune balance, where it inhibits CD 4+ T cell proliferation, promotes Th17 responses, and induces the secretion of IL-10 in human monocytes.…”
Section: Discussionsupporting
confidence: 92%
“…This finding was surprising considering the large number of molecules present in saliva, including salivary leptins, CCL5 (RANTES), IL‐1α, and KGF, which are described as mitogens (Dawes et al, ; Groschl et al, ; Kroeze et al, ). However, it must also be considered that cytotoxic proteins such as LL37, as mentioned above, are also present in saliva, indicating that a delicate balance exists between mitogens and antimicrobial proteins (Boink et al, ). It has been shown that a prolonged acidic wound environment can prevent wound closure and re‐epithelialization (Kruse et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we have shown that histatin 1 and LL37 (both salivary peptides) stimulate inflammatory cytokine release from keratinocytes, the latter via an IL-1α-dependent pathway (Boink et al, 2017). Since IL-1α is pre-stored in the stratum corneum and is also readily synthesized by keratinocytes, it is most probable that saliva stimulates pro-inflammatory cytokine release from keratinocytes, which in turn stimulates an inflammatory cytokine cascade via the fibroblasts (Boink et al, 2017;Dawes et al, 2015;Spiekstra, Breetveld, Rustemeyer, Scheper, & Gibbs, 2007). Such an effect would be even more pronounced in the presence of a wound.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations